2017
DOI: 10.1039/c7ra10150c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sulfamethoxazole degradation in soil by immobilized sulfamethoxazole-degrading microbes on bagasse

Abstract: The presence of sulfamethoxazole (SMX) in the environment is becoming a serious problem because of its toxicity and high risk to human health and microbial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Larcher and Yargeau (2011) reported that the arylamine N-acetyltransferase, which shows high specificity for aromatic amines, is involved in the degradation of SMX in P. aeruginosa and Rhodococcus species. Hu et al (2017) proposed the pathways of SMX degradation by Enterobacter cloacae strain T2. The initial metabolites of SMX biodegradation follow four pathways: methylation, substitution by hydroxyl and double bond oxidation, desulphurization and acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…Larcher and Yargeau (2011) reported that the arylamine N-acetyltransferase, which shows high specificity for aromatic amines, is involved in the degradation of SMX in P. aeruginosa and Rhodococcus species. Hu et al (2017) proposed the pathways of SMX degradation by Enterobacter cloacae strain T2. The initial metabolites of SMX biodegradation follow four pathways: methylation, substitution by hydroxyl and double bond oxidation, desulphurization and acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…This further confirms that the presence of a biofilm had a positive effect on SMX removal, especially considering that byproducts deriving from SMX partial biodegradation could have a higher hydrophobicity and therefore, higher affinity for the biofilm. Reis et al listed over 10 main byproducts of SMX deriving from bacterial degradation in both aerobic and anaerobic conditions, while Hu et al analyzed over 20 SMX metabolites in a degradation study carried out with two bacterial strains isolated from pig slurry [36,42]. For example, 4-Nitrophenol, 4-Nitro-sulfamethoxazole, Acetanilide, Phenylacetic acid and Benzoic acid (SMX metabolites) have log K ow values of 1.91, 1.22, 1.16, 1.41 and 1.87 respectively.…”
Section: Fate Of Radiolabeled Smxmentioning
confidence: 99%
“…40,41 Compared with other biomass carrier materials, sugarcane bagasse has some advantages: (1) reduction of the mass transfer of cells due to its highly porous nature; (2) suitability for gas evolution during cell growth; (3) it is nontoxic; (4) it is easily available; (5) provides carbon and energy for cell growth. [41][42][43] In this research, some potential bio-carrier materials were investigated for determining an optimal carrier (peanut shell and straw). Finally, sugarcane bagasse was employed as a matrix for cell immobilization to degrade SD on the basis of the cell immobilization status.…”
Section: Introductionmentioning
confidence: 99%